2014
DOI: 10.1016/j.jpha.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

UPLC-Q-TOF/MS based metabolomic profiling of serum and urine of hyperlipidemic rats induced by high fat diet

Abstract: Hyperlipidemia is considered to be a high lipid level in blood, can induce metabolic disorders and dysfunctions of the body, and results in some severe complications. Therefore, hunting for some metabolite markers and clarifying the metabolic pathways in vivo will be an important strategy in the treatment and prevention of hyperlipidemia. In this study, a rat model of hyperlipidemia was constructed according to histopathological data and biochemical parameters, and the metabolites of serum and urine were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 35 publications
(49 reference statements)
3
14
0
Order By: Relevance
“…Because glycolysis is suppressed and gluconeogenesis is upregulated in the HFD group [ 36 ], monosaccharides were anticipated to increase in the urine of the HFD group. In previous findings, the alteration of pseudouridine, creatinine, taurine, and hippuric acid levels in HFD group showed similar patterns when compared to our results [ 36 , 37 ]. According to one study, HFD intake was related to an increase in lipid oxidation, lipid accumulation, and changes in choline, purine, and amino acid metabolism.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Because glycolysis is suppressed and gluconeogenesis is upregulated in the HFD group [ 36 ], monosaccharides were anticipated to increase in the urine of the HFD group. In previous findings, the alteration of pseudouridine, creatinine, taurine, and hippuric acid levels in HFD group showed similar patterns when compared to our results [ 36 , 37 ]. According to one study, HFD intake was related to an increase in lipid oxidation, lipid accumulation, and changes in choline, purine, and amino acid metabolism.…”
Section: Resultssupporting
confidence: 90%
“…Many researchers also suggest that the alteration of gut microbiota by HFD exacerbates inflammation and obesity [ 30 , 32 ]. Hippuric acid is derived from phenylalanine, and its metabolite is represented in a lower proportion in the urine of the HFD group due to the modulation of the gut microbiota population [ 37 ]. The results of the comparison of GC-TOF-MS results in the ND and HFD group suggested that the alteration of these metabolites was associated with overall metabolic dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…This might be due to disturbed gut microbiota metabolism under diabetic status [ 70 ]. As reported, concentrations of hippuric acid were lower in HFD-induced hyperlipidemic rats than in normal rats [ 71 ]. d -glucurono-6,3-lactone, participating in ascorbate and aldarate metabolism, was increased in T2DM rats and was downregulated after treatment of SR, CR and their combined extracts.…”
Section: Discussionmentioning
confidence: 72%
“…Biochemical parameters including total bilirubin (T-BIL), total protein (TP), albumin (ALB), alanine transaminase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), glucose (GLU), triglycerides (TG) and total cholesterol (TCH), low density lipoprotein cholesterol (LDL) and high density lipoprotein cholesterol (HDL), were analyzed in the experiment. The AI was calculated as followed: AI = (TCH - HDL)/HDL 24 . The kits for biochemistry analysis were provided by Ningbo Medical System Biotechnology Co., Ltd (Ningbo, China).…”
Section: Methodsmentioning
confidence: 99%